Screening Pendayagunaan Biskuit Ikan Sori + Kelor Sebagai Pangan Fungsional Pada Remaja di Daerah Pesisir Desa Bajo Indah, Kecamatan Soropia, Kabupaten Konawe - Fatmawati, Fatmawati; Koro, Suriana; Petrus, Petrus; Abadi, Ellyani; Dwi Putri, Tenri Zulfa Ayu (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2024)
Sori fish is one of the seafood sources of animal protein which is a local food in coastal areas that is still rarely consumed by the community, likewise with moringa is a functional food that is easy to obtain and process for malnutrition (wasting), KEK and anemia. Providing Moringa Biscuits is an innovation that is useful for preventing adolescent nutritional problems. The purpose of this service is to provide counseling and additional food in the form of Sori Fish + Moringa biscuits as Functional food for Adolescents in the Coastal Area of ​​Bajo Indah Village. The service method is carried out by lectures and questions and answers. This service was carried out on August 28, 2024 in the coastal area of ​​Bajo Indah Village, precisely at SMPN Satu Atap 1 Soropia. The target of this activity is adolescents (students) registered at SMPN Satu Atap 1 Soropia as many as 30 people. Data on the use of biscuits and knowledge were collected using a questionnaire and processed using the Wilcoxon sign rank test. The results of community service showed that before counseling and giving biscuits, 20% of teenagers utilized sori fish and moringa and after counseling and giving sori fish and moringa biscuits, 100% of teenagers utilized biscuits. Knowledge before counseling obtained an average pretest score of 4 and after counseling obtained an average posttest score of 8. The test results obtained a significance of 0.000. This conclusion is that the provision of sori fish and moringa biscuits and counseling can increase the utilization and knowledge of teenagers about the use of sori fish and Moringa (Moringa Oliefera Lam) as functional foods. This community service suggests that schools need to provide routine education to teenagers to utilize local foods in the form of sori fish and moringa.